Leg Venous Properties in Children With Myelomeningocele - Domagalska–Szopa, Małgorzata; Szopa, Andrzej; Puchner, Maximilian; Schreiber, Lutz; Siwiec, Andrzej; Hagner-Derengowska, Magdalena; Ziaja, Damian (Frontiers in Pediatrics, 2020)
Introduction. The vascular properties of individuals with myelomeningocele (MMC) are an underestimated problem, as evidenced by the lack of relevant research. Therefore, this study was conducted to assess the venous properties of the leg in children with MMC. This study compared the duration of retrograde flow (RF) of the distal and proximal sites of the great saphenous vein (GSV) in children with MMC and typically developing (TD) children. Additionally, the impact of MMC clinical features, such as the anatomical level of the spinal cord defect, muscle strength of the lower limbs, and level of gross motor functional abilities on the of GSV sufficiency were assessed. Methods. Thirty ambulant children between 7–12 years with MMC and an age- and sex-matched sample of thirty children with typical development (TD) were included in the study. All participants underwent a complete physical examination that included gross motor assessment, manual muscle testing, and duplex ultrasound examination of the GSV reflux. The duration of retrograde flow (RT) in the GSV was evaluated at four sites: P1: proximal thigh; P2: medial thigh; P3: upper leg; and P4: lower leg. The measurements were performed in two body positions: horizontal position (HP) and vertical position (VP). Results. Children with MMC showed increased duration of RT of both the proximal and peripheral sites of GSV, as compared with the TD peers. The prevalence of GSV reflux in peripheral segments was significantly higher than in the proximal segments. The severity of MMC (expressed by higher level of the spinal cord defect), deficit of thigh and leg muscle strength, and lower functional independence negatively influenced the GSV sufficiency in patients with MMC. Gravity directly influenced GSV reflux occurrence and reflux hemodynamic parameters in MMC. Conclusion. These findings may help guide further prospective studies to more clearly delineate the risk of developing venous insufficiency in children with MMC and determine better screening, prevention, and treatment algorithms for venous insufficiency in patients with SB.